English Proficiency as a Key to Effective Communication in MultilingualCustomer Service Environments Call senter - Nova Aryani; Nayla Juanita; Eliyana Wulandari (Proceedings Law, Accounting, Business, Economics and Language, 2025)
This study investigates the role of English proficiency in enhancing communication effectiveness within multilingual customer service environments, particularly in call centers. Using a Systematic Literature Review (SLR) approach, the study analyzes recent research on English language skills, communication challenges, and service performance in global customer service contexts. The findings reveal that beyond basic language knowledge, effective listening, comprehension of diverse accents, and cultural adaptability are critical for maintaining service quality and customer satisfaction. Furthermore, the study highlights theneed for targeted language training that emphasizes practical communication strategies and exposure to various English varieties. These insights provide valuable recommendations for organizations seeking to improve customer service performance and develop effective language support policies for frontline employees in high-pressure, multilingualenvironments.